Influence of specialty on post space preparation - Hamza Alsharief; Nizar Mohammed Ahmed; Feras Aalam; Adel Alharbi; Hiba Gari; Mohammad Alhashmy Alamer; Amjad Omar Alsiyud (International Journal of Medical Toxicology and Legal Medicine, 2024)
Aim and Objectives: Intraradicular posts are provided to retain coronal restoration in root canal treated teeth. The retention they provided can be influenced by many factors including length, accuracy of fit and diameter of the post.To measure the minimum residual thickness of proximal root walls of teeth prepared with two different specialty dentists, endodontist and prosthodontics. Methodology: Twenty extracted human single-rooted teeth with oval cross section where instrumented and filled with gutta-percha and sealer.The sample allocated to 2 operators. Endodontist (OP1) and prosthodontists (OP2), of clinical experience of more than 10 years as specialist.Each operator will prepare 10 teeth for tapered post channels (RTD DT fibre post).then roots were sectioned horizontally at three levels, apical, middle and coronal.And digital measure of the minimum residual dentine thickness done by simple linear measurements s. Results: Prosthodontist shows more incidence of minimum RDT measurements at all segment levels than endodontists. Conclusion: Within limitation of this this study, clinician philosophy in post size selection and its preparation technique could have influence on remaining dentine thickness.